Penerapan Teks Narasi Goa Kreo Berbasis Culturally Responsive Teaching Berbantuan Media Puzzle Upaya Peningkatan Hasil Belajar dan Berpikir Kritis Siswa Kelas III SD - Lailatul Hikmah; Panca Dewi Purwati (Journal on Education, 2025)
This study aims to analyze the improvement of students' learning outcomes and critical thinking skills through the application of Goa Kreo narrative text based on the Culturally Responsive Teaching (CRT) approach with puzzle media. The subjects of the study were grade III students of SDN Kalibanteng Kidul 01 Semarang. The study used a pre-experimental design with a quantitative and qualitative approach. The results showed an increase in student learning outcomes with an average N-gain of 0.46, included in the moderate category. In addition, students' critical thinking skills also increased significantly based on observation sheets that were analyzed descriptively. The CRT approach has proven effective in integrating local culture into learning.